Sex-Based Differences in the Cytokine Production and Intracellular Signaling Pathways in Patients With Rheumatoid Arthritis - Uday P. PRATAP,; Lalgi HIMA,; Thangamani KANNAN,; Chadrasekaran THYAGARAJAN,; Hannah P. PRIYANKA,; Ramasamy VASANTHAREKHA,; Anand PUSHPARANI,; Srinivasan THYAGARAJAN, (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate lymphoproliferation, cytokine production, and intracellular signaling molecules in peripheral blood mononuclear cells (PBMCs) isolated from healthy individuals and rheumatoid arthritis (RA) patients to understand the extent of the involvement of these pathways in the pathogenesis of RA. Patients and methods: The study included 65 participants (29 males, 36 females; mean age 51.8±10.3 years; range, 37 to 71 years) who were categorized into four groups as healthy males (n=22, mean age 49.8±10.6 years; range, 39 to 65 years), male RA patients (n=7, mean age 51.8±13.9 years; range, 37 to 68 years), healthy females (n=20, mean age 53.7±8.8 years; range, 42 to 67 years), and female RA patients (n=16, mean age 52.9±10.4 years; range, 40 to 71 years). PBMCs were collected from the participants and analyzed for Concanavalin A (Con A)-induced lymphoproliferation using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay, cytokine production, and phospho-signal transducer and activator of transcription 3 (p-STAT-3), phospho-extracellular-signal-regulated kinase (p-ERK), phospho-cAMP response element binding (p-CREB), and phospho-protein kinase B expressions using enzyme-linked immunosorbent assay. Short form of the Arthritis Impact Measurement Scales 2 and multidimensional health assessment questionnaire were used to measure the level of disability and the quality of life. Results: In RA patients, production of Con A-induced interleukin (IL)-2 and IL-17 was higher in both sexes while interferon-gamma levels decreased in RA females alone. Expression of p-STAT-3 in PBMCs increased in RA males while it was unaltered in RA females. p-ERK expression was not altered while p-CREB expression was enhanced in RA males and females. Protein-protein interaction analyses demonstrated that these and other key signaling molecules were dysregulated in RA patients. Conclusion: Our results suggest that sex-based differences in RA pathogenesis result from differential alterations in signaling pathways to influence the inflammatory process.